Report on a Reconnaissance Visit to Examine Mineralization in the Cordillera Fueguina, Tierra del Fuego, Argentina - Marquéz, Marcelo J.; Sangster, Donald F. (Servicio Geológico Minero Argentino. Instituto de Geología y Recursos Minerales., 2001)
Fil: Marquéz, M. Servicio Geológico Minero Argentino. Instituto de Geología y Recursos Minerales; Argentina. Fil: Sangster, D.F. Servicio Geológico Minero Argentino. Instituto de Geología y Recursos Minerales; Argentina. This report describes observations made of metallic mineralization in the Cordillera Fueguina, Tierra del Fuego province. These activities relied on the collaboration and logistic support of Yamana Resources loe. who, through the cooperation of resident geologist Ken Gibson, allowed the authors access to ali information obtained during exploration in the last three years. The work during the field trip between FebruarylO -13, 1998 consisted of: A) the examination of mineralized drill core intersections from the Arroyo Rojo and Sargent prospects and a review of geological reports and maps; B) geological reconnaissance of the Beatrice mine and Lapataia areas, and C) reconnaissance of the geology and mineralized areas ofthe Monte Olivia and Río Hambre. Toe most important objective was to define the mineralization characteristics and, if possible, to suggest a preliminary genetic model.